2015
DOI: 10.1002/2014gl062555
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of existence of the small-scale field-aligned currents in middle and low latitudes and an estimate of time scale of their temporal variation

Abstract: The magnetic data obtained by the SWARM (the Earth's Magnetic Field and Environment Explorers) satellites in middle or low latitudes during the initial 2 months after launch were analyzed, when they flew nearly on the same orbit with variable time separation ranging from 5 to 100 s. It was confirmed that the small-scale magnetic fluctuations having period around 10-30 s are the manifestation of spatial structure of small-scale field-aligned currents along the orbits. From the statistical relation between corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 10 publications
7
24
0
Order By: Relevance
“…As mentioned in "Introduction" section, Iyemori et al (2015) confirmed that the MRs having period around 10-30 s observed almost all the time along the satellite orbit by Swarm satellites are the spatial structures of small-scale FACs, and they also suggested that the typical timescale of the magnetic fluctuations is about 200, 296 and 340 s for the meridional component and 340 s for the zonal component. Nakanishi et al (2014) suggested that the small-scale FACs observed by CHAMP are caused by the ionospheric E-layer dynamo having the lower atmospheric origin.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As mentioned in "Introduction" section, Iyemori et al (2015) confirmed that the MRs having period around 10-30 s observed almost all the time along the satellite orbit by Swarm satellites are the spatial structures of small-scale FACs, and they also suggested that the typical timescale of the magnetic fluctuations is about 200, 296 and 340 s for the meridional component and 340 s for the zonal component. Nakanishi et al (2014) suggested that the small-scale FACs observed by CHAMP are caused by the ionospheric E-layer dynamo having the lower atmospheric origin.…”
Section: Discussionsupporting
confidence: 65%
“…Iyemori et al (2015) confirmed that the MRs observed by Swarm satellites on the initial orbits are spatial structure of FACs. Timescale of their temporal variations is roughly estimated to Open Access *Correspondence: aoyama@kugi.kyoto-u.ac.jp 1 Graduate School of Science, Kyoto University, Kyoto, Japan Full list of author information is available at the end of the article be 200-340 s, and amplitudes of the MRs shown in their paper are about 1 nT.…”
Section: Introductionsupporting
confidence: 71%
“…Additionally, Swarm data are used to study the Sun's influence on the Earth system by analyzing electric currents in the magnetosphere and ionosphere and understanding the impact of solar wind on the dynamics of the upper atmosphere. Swarm currently offers one of the best-ever surveys of the Earth's main and crustal magnetic field (Civet et al, 2015;De Michelis et al, 2015;Hulot et al, 2015;Olsen et al, 2015;Schnepf et al, 2015) as well as the near-Earth electromagnetic environment (Alken et al, 2015;Archer et al, 2015;Buchert et al, 2015;Dunlop et al, 2015;Goodwin et al, 2015;Iyemori et al, 2015;Lühr et al, 2015a, b;Park et al, 2015;Pitout et al, 2015;Spicher et al, 2015). The interested reader is also referred to the special issue "Swarm science results after 2 years in space" (for details, see Olsen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The perturbations of the total electron content are predicted to be detectable by groundbased radar and GPS receivers. Acoustic waves also drive field-aligned currents that may be detectable by in situ magnetometers (Iyemori et al, 2015). A recent paper (Zettergren and Snively, 2015) reports that the recent measurements of GPS-derived TEC reveals acoustic wave periods from ∼ 1 to 4 min in the F-region ionosphere following natural hazard events, such as earthquakes, severe weather fronts, and volcanoes.…”
mentioning
confidence: 99%
“…Moreover, in order to search the seismogenic effects in the ionosphere, it is necessary to unify the well-developed model of the electromagnetic channel to seismo-ionospheric coupling (Molchanov et al, 1995;Rapoport et al, 2004b;Grimalsky et al, 1999;Pulinets and Boyarchuk, 2004;Sorokin and Hayakawa, 2013) with the model of the acoustic channel (Gokhberg and Shalimov, 2000;Rapoport et al, 2004aRapoport et al, , 2009Koshevaya et al, 2002;Grimalsky et al, 2003;Zettergren and Snively, 2015;Iyemori et al, 2015). Traditionally, AGWs and electromagnetic waves have been considered as the basis of two main competitive mechanisms of seismo-ionospheric coupling (Sorokin and Hayakawa, 2013;Klimenko et al, 2011;Pulinets and Boyarchuk, 2004).…”
mentioning
confidence: 99%